Effects of Fe supplementation in newborn and nursery pigs on growth performance and hematological criteria - Williams, Hayden Ervin (Kansas State University, 2020)
This dissertation consists of 4 chapters involving studies with administration of Fe dosage and the timing of Fe administration after birth in newborn pigs, source of Fe supplementation in nursery pigs, and feeding high levels of SID Trp:Lys ratios with ractopamine HCL in finishing pigs. Chapter 1 involved an experiment that used 336 newborn pigs to determine the effects of increasing injectable Fe dosage provided from gleptoferron after birth on suckling and subsequent nursery performance and blood criteria. The results suggest that providing 100 mg of Fe from gleptoferron is sufficient to support growth up to weaning but providing 200 mg of Fe from gleptoferron optimizes subsequent nursery growth performance and pre- and postweaning hematological criteria. The results further suggest providing an additional 100 mg of Fe from gleptoferron on d 11 of age result in no evidence for an effect on pre- or postweaning growth performance but increased hematological criteria at weaning and 14 d in the nursery. Chapter 2 involved two experiments that used 2,216 newborn pigs to determine the effects of age of newborn pigs receiving a Fe injection on suckling and subsequent nursery and growing-finishing growth performance and blood criteria. The results suggest that providing 200 mg of Fe from gleptoferron between d 1 and 7 after farrowing is sufficient for optimizing pre and post-weaning growth performance. The results further suggest that providing an additional 200 mg of Fe from gleptoferron 12 d after birth resulted in no evidence for an effect on preweaning growth performance but increased hematological criteria at weaning. Chapter 3 involved one experiment that used 140 Fe-deficient weanling pigs evaluating Fe sources (FeSO₄ or FeCO₃) and level (10 to 50 mg/kg) on nursery growth performance and hematological criteria. The results showed that the micronized form of FeCO₃ is a sufficient alternative source of Fe that can be added to nursery diets to meet post-weaning Fe requirements. The results also suggest that the Fe deficient model utilized was sufficient in evaluating the availability of the 2 different Fe sources and their effects on nursery pig growth performance and hematological criteria. Chapter 4 had 1 experiment that used 1,791 finishing pigs to determine the effects of high SID Trp:Lys ratios in diets containing ractopamine HCL. The results suggested that increasing the SID Trp:Lys ratio above 20% that provided Trp intake above the NRC (2012) requirement of 4.1 g/d showed no evidence for an improvement in growth performance or carcass characteristics.
Keywords: Fe; gleptoferron; growth performance; swine